Revitalized urban areas as tourist attractions in Łódź - Jakóbczyk-Gryszkiewicz, Jolanta (Turystyka – to znaczy co? Uroboros czy Feniks, 2025)
The work presents the most interesting examples of the revitalization of 19th century urban space in Łódź and its open spaces. The historic factories, as well as its residential buildings, were significantly degraded in the 1990s after the collapse of the city’s leading textile industry. At the beginning of the 21st century, the city government using EU funds, and private investors including foreign companies, began its large-scale revitalization, preserving the architecture of the buildings and introducing new functions to these areas – mainly services – including tourism, housing and communication. The scale of these activities, especially in post-industrial areas, is large and, as in the case of the newly established Manufaktura centre, the largest even in Europe. The aim of the study was to indicate that the revitalized post-industrial, residential and natural areas have become attractive for tourists and are a kind of showcase for modern Łódź.